ANALISIS KESULITAN HASIL TES SISWA SMP KELAS VIII PADA MATERI SEGIEMPAT DITINJAU DARI PROFIL KETERAMPILAN GEOMETRI (PKG) - Ra'uf Azhar Fakhrudin; Wahyu Hidayat; Linda Linda (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2023)
This study aims to analyze students' difficulties in solving questions on quadrilateral material based on the stages of geometry skills using a descriptive method. The subjects of this study were 27 students of class VIII SMP Sumur Bandung Cililin. The instruments in this study were interview guidelines and 5 essay test questions. Data collection techniques used are observation, interviews, and documentation. The data analysis uses the formula for the percentage of student answers with the help of Microsoft Excel. From the results of this study it was found that in the visual stage the average student score was 69.00%, in the verbal stage it was 69.00%, in the drawing stage it was 79.00%, in the logic stage it was 46.00%, and in the applied average student score of 50.00%. Based on the results of these test items, it shows that in solving quadrilateral questions there are still difficulties felt by students in terms of geometry skills.